A reference electrode for testing valve-regulated lead-acid batteries and its preparation method and application

By using a filamentous reference electrode body composed of silver wire and silver sulfate film in a valve-controlled lead-acid battery, the problem that the prior art cannot work stably in a flowless electrolyte environment for a long time is solved, the need for electrochemical testing is achieved, and a reference electrode suitable for industrial lead-acid battery is provided.

CN115117487BActive Publication Date: 2025-02-28NORTH CHINA ELECTRICAL POWER RES INST +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202210460363.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-04-28
Publication Date
2025-02-28
Estimated Expiration
2042-04-28

AI Technical Summary

Technical Problem

The prior art cannot be effectively used for electrochemical testing of valve-controlled lead-acid batteries because its reference electrode cannot operate stably in a flowless electrolyte environment for a long time and cannot meet the hardness and performance requirements of industrial testing.

Method used

A filamentous bare reference electrode body consisting of silver wire and a silver sulfate film layer coated on the surface of the silver wire is used. The reference electrode body forms a silver sulfate film layer in a concentrated sulfuric acid solution through a three-electrode electrochemical test system to ensure its stability and conductivity in a strong acid environment.

Benefits of technology

The reference electrode is realized for a long-term and stable operation inside the valve-controlled lead-acid battery, without affecting the normal charging and discharging process of the battery, and meets the needs of electrochemical testing, providing a reference electrode suitable for electrochemical performance testing of industrial lead-acid batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115117487B_ABST
    Figure CN115117487B_ABST
Patent Text Reader

Abstract

The present invention provides a reference electrode for testing a valve-regulated lead-acid battery, and a preparation method and application thereof. The reference electrode is provided with a filamentary exposed reference electrode body, which is composed of a silver wire and a silver sulfate film layer coated on the surface of the silver wire; the diameter of the silver wire is 0.5-2 mm, and the length of the silver wire coated by the silver sulfate film layer is 100-200 mm; the length of the silver wire is greater than the length of the silver wire coated by the silver sulfate film layer; the silver sulfate film layer is a silver sulfate film layer prepared by the following method: using the silver wire as a working electrode, a platinum electrode as an auxiliary electrode, and a saturated calomel electrode as a reference electrode; performing an anodic polarization treatment on the working electrode in a sulfuric acid solution to form a silver sulfate film layer on the surface of the silver wire; the sulfuric acid solution is concentrated sulfuric acid with a mass concentration of 95%-98%, and a polarization current density of 5-7 mA / cm 2 , the polarization time is 18-22s. This reference electrode can be stably applied to electrochemical testing of valve-regulated lead-acid batteries for a long time.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a reference electrode for testing a valve-regulated lead-acid battery and a preparation method and application thereof. Background Art

[0002] The battery is an indispensable device for the DC system of power grids and power plants. It is responsible for supplying DC loads to important equipment such as relay protection, automatic devices, automation equipment, and circuit breaker tripping and closing mechanisms. When the AC power fails, the charger cannot output DC power. The battery is the only DC power source to supply power to the DC load. Therefore, the battery pack is the core of the DC power supply system, and its performance quality is related to the safe and stable operation of power grid equipment. Valve-regulated lead-acid batteries are widely used in power grids due to their low cost, safe and stable operation, and their application accounts for more than 90%.

[0003] At present, the single-cell voltage of valve-regulated lead-acid batteries is mainly 2V. The battery pack used as the backup power supply of the substation is composed of multiple valve-regulated lead-acid batteries in series. The design life of the valve-regulated lead-acid batteries in the battery pack commonly used in the substation is usually 10-12 years (some manufacturers claim that the floating charge life is 15 years), but in actual use, the battery life is far lower than the design value. During the operation of the valve-regulated lead-acid battery, problems such as battery aging, increased internal resistance, reduced capacitance, battery leakage, and corrosion of the terminal will occur. In order to ensure the safe, stable and efficient operation of the battery pack, it is necessary to conduct performance evaluation tests such as battery standard capacity, large current charging and discharging fast capacity, group consistency, and battery accelerated aging. At present, the performance evaluation test of the battery usually tests the working voltage and discharge capacity outside the battery, and there are few reports on the internal failure mechanism that causes the hidden dangers of the valve-regulated lead-acid battery. The reaction mechanism inside the battery directly reflects the thermodynamic and kinetic state of the battery system, and is the basis for comprehensive battery performance evaluation.

[0004] The study of the internal reaction mechanism of the battery requires the testing of the electrode potential and polarization resistance of the positive and negative electrode reactions inside the battery. In this process, the potential stability of the reference electrode is the key. Due to the closed shell of the valve-regulated lead-acid battery, the oxygen cycle formed inside the battery, and the lack of free electrolyte inside, the existing reference electrodes cannot meet the needs of electrochemical testing of industrial lead-acid batteries.

[0005] Since the reference electrode usually needs to be fixed in the electrolyte circulation pipeline to realize the electrochemical test of the battery, and the valve-regulated lead-acid battery electrolyte is absorbed in the separator made of ultra-fine glass fiber, and there is no external electrolyte circulation pipeline, there is no report in the prior art on the electrochemical test of the valve-regulated lead-acid battery using the reference electrode. There is no free electrolyte inside the valve-regulated lead-acid battery, and the electrolyte is absorbed and stored in the separator between the positive and negative plates. The material of the separator is ultra-fine glass fiber cotton and the thickness is 10mm. The existing reference electrode cannot be used for the electrochemical test of industrial lead-acid batteries.

[0006] Since the lead-acid battery electrolyte contains 15%-40% sulfuric acid (with a small amount of iron, manganese, and copper added), it is highly corrosive. Most commonly used reference electrodes, such as glass reference electrodes, contain reference solutions that will be contaminated if left in the lead sulfate system for a long time, and need to be removed and replaced in time, resulting in most commonly used reference electrodes being unable to be used in lead-acid batteries for a long time. Although some reference electrodes are suitable for sulfuric acid media, such as mercuric sulfate or mercurous chloride reference electrodes, most of them are designed for laboratory experiments, and their performance and structure cannot meet the requirements of industrial valve-regulated lead-acid battery testing.

[0007] In summary, it is currently necessary to develop a reference electrode that can be stably applied to the electrochemical testing of valve-regulated lead-acid batteries to meet the testing requirements of valve-regulated lead-acid batteries. Summary of the invention

[0008] The object of the present invention is to provide a reference electrode which can be stably applied to electrochemical testing of valve-regulated lead-acid batteries for a long time and a method for preparing the reference electrode which can be stably applied to electrochemical testing of valve-regulated lead-acid batteries for a long time.

[0009] In order to achieve the above-mentioned object, the present invention provides a reference electrode for testing a valve-regulated lead-acid battery, wherein the reference electrode is provided with an exposed reference electrode body;

[0010] The exposed reference electrode body is in a filament shape, and is composed of a silver wire and a silver sulfate film layer coated on the surface of the silver wire;

[0011] The diameter of the silver wire is 0.5-2 mm, and the length of the silver wire coated with the silver sulfate film layer is 100-200 mm; the length of the silver wire is greater than the length of the silver wire coated with the silver sulfate film layer;

[0012] The silver sulfate film layer is selected from the silver sulfate film layer prepared by the following preparation method:

[0013] A three-electrode electrochemical test system is formed by using a silver wire as a working electrode, a platinum electrode as an auxiliary electrode, and a saturated calomel electrode as a reference electrode; the working electrode in the three-electrode electrochemical test system is subjected to an anodic polarization treatment in a sulfuric acid solution to form the silver sulfate film layer on the surface of the silver wire; wherein the sulfuric acid solution is concentrated sulfuric acid (usually analytical pure sulfuric acid can be selected) with a mass concentration (based on the total mass of the sulfuric acid solution) of 95%-98%, and the polarization current density is 5-7 mA / cm 2 , polarization time is 18-22s.

[0014] The outer shell of the valve-regulated lead-acid battery is sealed, and the electrolyte is absorbed in the ultra-fine glass fiber partition. There is no flowing electrolyte, and the internal electrolyte is a strong acid system. The existing reference electrodes are usually large in size and cannot be placed inside the valve-regulated lead-acid battery. The reference electrode body of the existing reference electrode is usually encapsulated and cannot be used in an environment without flowing electrolyte. Even if the existing reference electrode is reduced in size and the encapsulation is removed, it is not suitable because it cannot meet the hardness and performance requirements. The present invention creatively proposes a reference electrode with a special filamentary exposed silver / silver sulfate reference electrode body. The reference electrode can be placed inside the valve-regulated lead-acid battery, and the inserted reference electrode will not damage the structure and performance of the battery itself, and will not affect the normal charging and discharging process of the battery. The above-mentioned reference electrode for testing the valve-regulated lead-acid battery is installed in the valve-regulated lead-acid battery, and the internal pressure and battery shape of the battery remain consistent before and after, and the electrode potential of the reference electrode is stable for a long time.

[0015] In the above-mentioned reference electrode for testing valve-regulated lead-acid batteries, preferably, the diameter of the silver wire of the reference electrode body is 1 mm.

[0016] In the above-mentioned reference electrode for testing valve-regulated lead-acid batteries, preferably, the length of the silver wire coated with the silver sulfate film layer is 125 mm.

[0017] In the reference electrode for testing the valve-regulated lead-acid battery, preferably, the sulfuric acid solution is concentrated sulfuric acid with a mass concentration of 95%-98%, and the polarization current density is 6 mA / cm 2 , the polarization time is 20s.

[0018] In the above-mentioned reference electrode for testing valve-regulated lead-acid batteries, preferably, the length of the exposed reference electrode body is 250 mm.

[0019] In the above-mentioned reference electrode for testing valve-regulated lead-acid batteries, preferably, the silver purity of the silver wire of the reference electrode body is 99.9 wt % (based on the total mass of the silver wire).

[0020] In the above-mentioned reference electrode for testing valve-regulated lead-acid batteries, preferably, the silver purity of the silver wire of the reference electrode body is 99.9 wt % (based on the total mass of the silver wire).

[0021] In the above-mentioned reference electrode for testing valve-regulated lead-acid batteries, preferably, the reference electrode is further provided with a lead wire connected to the exposed reference electrode body.

[0022] In the above-mentioned reference electrode for testing valve-regulated lead-acid batteries, preferably, the step of performing anodic polarization treatment on the working electrode in the three-electrode electrochemical testing system in a sulfuric acid solution is performed using a PAR4000A electrochemical workstation.

[0023] The present invention also provides a method for preparing the reference electrode for testing the valve-regulated lead-acid battery, wherein the method comprises:

[0024] A three-electrode electrochemical test system was constructed with a silver wire as the working electrode, a platinum electrode as the auxiliary electrode, and a saturated calomel electrode as the reference electrode.

[0025] The working electrode in the three-electrode electrochemical test system is subjected to anodizing treatment in a sulfuric acid solution to form a silver sulfate film on the surface of the silver wire to prepare a reference electrode body; wherein the sulfuric acid solution is concentrated sulfuric acid (usually analytical pure sulfuric acid can be selected) with a mass concentration (based on the total mass of the sulfuric acid solution) of 95%-98%, and the polarization current density is 5-7 mA / cm 2 , polarization time is 18-22s;

[0026] The reference electrode body prepared as the exposed reference electrode body is used to prepare the reference electrode for testing the valve-regulated lead-acid battery.

[0027] In the above preparation method, preferably, the sulfuric acid solution is concentrated sulfuric acid with a mass concentration of 95%-98%, and the polarization current density is 6 mA / cm 2 , the polarization time is 20s.

[0028] In the above preparation method, preferably, the length of the silver wire is 250 mm.

[0029] In the above preparation method, preferably, the silver purity of the silver wire is 99.9wt% (based on the total mass of the silver wire).

[0030] In the above preparation method, preferably, the step of performing an anodic polarization treatment on the working electrode in the three-electrode electrochemical test system in a sulfuric acid solution is performed using a PAR4000A electrochemical workstation.

[0031] In the above preparation method, preferably, the reference electrode for testing the valve-regulated lead-acid battery is prepared by using the prepared reference electrode body as the exposed reference electrode body in the following manner: one end of the prepared reference electrode body is connected to a lead to prepare a reference electrode for testing the valve-regulated lead-acid battery.

[0032] The present invention also provides application of the reference electrode for testing valve-regulated lead-acid batteries in electrochemical testing of valve-regulated lead-acid battery electrodes.

[0033] In the above application, preferably, the above reference electrode for testing valve-regulated lead-acid battery is inserted into the valve-regulated lead-acid battery, so that the exposed reference electrode body of the above reference electrode for testing valve-regulated lead-acid battery contacts with the partition for absorbing electrolyte provided between the positive and negative plates of the valve-regulated lead-acid battery, and then the above reference electrode for testing valve-regulated lead-acid battery is used as a reference electrode to carry out electrochemical testing of valve-regulated lead-acid battery electrodes.

[0034] The present invention also provides a valve-regulated lead-acid battery, wherein a reference electrode is arranged inside the valve-regulated lead-acid battery, and the reference electrode arranged inside the valve-regulated lead-acid battery adopts the reference electrode for testing the valve-regulated lead-acid battery described above;

[0035] In the valve-regulated lead-acid battery, the silver sulfate film layer of the exposed reference electrode body of the reference electrode contacts a separator disposed between the positive and negative plates and absorbing electrolyte.

[0036] In view of the internal electrochemical performance test requirements of valve-regulated lead-acid batteries, the inventors focused on objective difficulties such as the sealing of the battery shell, the absorption of the electrolyte in the ultra-fine glass fiber separator, and the strong acid system of the electrolyte. They innovatively proposed the concept of inserting a filamentous silver / silver sulfate reference electrode of a specific size and a specific state, and then proposed the technical solution required for protection by the present invention. The reference electrode provided by the present invention can be installed inside a valve-regulated lead-acid battery, the electrode potential in the internal environment of the lead-acid battery can be kept stable for a long time, and the reference electrode does not affect the operation of the valve-regulated lead-acid battery after being installed inside the valve-regulated lead-acid battery, thus meeting the requirements for battery electrochemical testing. The problem that the existing reference electrodes are not applicable due to the sealing of the valve-regulated lead-acid battery shell, the absorption of the electrolyte in the ultra-fine glass fiber separator, and the strong acid system of the internal electrolyte is solved, which is helpful to realize the electrochemical performance test of the internal electrode of the valve-regulated lead-acid battery. The reference electrode provided by the present invention is provided with an exposed silver / silver sulfate reference electrode body, and the exposed silver / silver sulfate reference electrode body has a specific shape and state-specific size, and has the advantages of suitable size, hardness that meets the insertion requirements, excellent conductivity, good active material polarization space, and better stability of the strong acid electrolyte system of the lead-acid battery.

[0037] The reference electrode provided by the present invention has a stable electrode potential and can be well applied to the dielectric system of lead-acid batteries, filling the gap of reference electrodes for electrochemical performance testing of industrial lead-acid batteries, enriching the monitoring means for subsequent all-round monitoring and evaluation of battery status, and has broad application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0038] Figure 1 This is a structural diagram of a reference electrode for testing a valve-regulated lead-acid battery according to an embodiment of the present invention.

[0039] Figure 2A This is a microscopic morphology of the silver sulfate film layer of the reference electrode A in the embodiment of the present invention.

[0040] Figure 2B This is a microscopic morphology of the silver sulfate film layer of the reference electrode B in the embodiment of the present invention.

[0041] Figure 2C This is a microscopic morphology of the silver sulfate film layer of the reference electrode C in the embodiment of the present invention.

[0042] Figure 3 Graph showing the electrode potential test results of reference electrode A, reference electrode B, and reference electrode C in an embodiment of the present invention.

[0043] Figure 4A This is a microscopic morphology of the silver sulfate film layer of the reference electrode D in the embodiment of the present invention.

[0044] Figure 4B This is a microscopic morphology of the silver sulfate film layer of the reference electrode E in the embodiment of the present invention.

[0045] Figure 4C This is a microscopic morphology of the silver sulfate film layer of the reference electrode F in the embodiment of the present invention.

[0046] Figure 5 This is a graph showing the electrode potential test results of reference electrode D, reference electrode E, and reference electrode F in an embodiment of the present invention.

[0047] Figure 6 This is a graph showing the stability test results of reference electrode G-1, reference electrode G-2, reference electrode G-3, reference electrode G-4, reference electrode G-5, and reference electrode G-6 in an embodiment of the present invention.

[0048] Figure 7 Graph showing the test result of the positive electrode potential of a valve-regulated lead-acid battery using the reference electrode K as the reference electrode in an embodiment of the present invention.

[0049] Figure 8 These are morphological diagrams of reference electrode G-1, reference electrode G-2, reference electrode G-3, reference electrode G-4, reference electrode G-5, and reference electrode G-6 in the embodiments of the present invention.

[0050] Fig. 9 It is a battery charge and discharge voltage-time curve diagram before and after the reference electrode is packaged in an embodiment of the present invention.

[0051] Fig.10 It is a battery charge and discharge capacity-time curve diagram before and after the reference electrode is packaged in an embodiment of the present invention. DETAILED DESCRIPTION

[0052] In order to make the purpose, technical solution and advantages of the embodiment of the present invention clearer, the technical solution in the embodiment of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiment of the present invention. Obviously, the described embodiment is a part of the embodiment of the present invention, not all of the embodiments. Based on the embodiment of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work belong to the protection scope of the present invention.

[0053] Since the valve-regulated lead-acid battery has a sealed shell, the electrolyte is absorbed in the ultra-fine glass fiber separator, there is no flowing electrolyte, and the internal electrolyte is a strong acid system, the existing reference electrodes are not applicable, which makes it difficult to test the electrochemical performance of the internal electrodes of the valve-regulated lead-acid battery. The present invention aims at the demand for testing the internal electrochemical performance of valve-regulated lead-acid batteries, focuses on the objective difficulties such as the sealing of the battery shell, the absorption of the electrolyte in the ultra-fine glass fiber separator, and the strong acid system of the electrolyte, and proposes the technical solution claimed by the present invention.

[0054] See also Figure 1 An embodiment of the present invention provides a reference electrode for testing a valve-regulated lead-acid battery, wherein the reference electrode is provided with a bare reference electrode body 1; the bare reference electrode body 1 is filamentous, and consists of a silver wire 11 and a silver sulfate film layer 12 coated on the surface of the silver wire 11; the diameter of the bare reference electrode body 1 is 0.5-2 mm (for example, 1 mm), and the length of the silver sulfate film layer 12 is 100-200 mm (for example, 125 mm); the length of the silver wire 11 is greater than the length of the silver sulfate film layer 12.

[0055] The silver sulfate film layer 12 is a silver sulfate film layer prepared by the following preparation method: a three-electrode electrochemical test system is formed by using a silver wire as a working electrode, a platinum electrode as an auxiliary electrode, and a saturated calomel electrode as a reference electrode; the working electrode in the three-electrode electrochemical test system is subjected to an anodic polarization treatment in a sulfuric acid solution to form the silver sulfate film layer 12 on the surface of the silver wire; the sulfuric acid solution is a concentrated sulfuric acid with a mass concentration (based on the total mass of the sulfuric acid solution) of 95%-98% (usually analytical pure sulfuric acid can be selected), and the polarization current density is 5-7 mA / cm 2, the polarization time is 18-22s; (for example, the sulfuric acid solution is concentrated sulfuric acid with a mass concentration of 95%-98%, and the polarization current density is 6mA / cm 2 , polarization time is 20s).

[0056] Furthermore, the length of the bare reference electrode body 1 is 250 mm.

[0057] Furthermore, the silver purity of the silver wire of the reference electrode body 1 is 99.9 wt % (based on the total mass of the silver wire).

[0058] Furthermore, the silver purity of the silver wire is 99.9 wt % (based on the total mass of the silver wire).

[0059] Furthermore, the step of performing an anodic polarization treatment on the working electrode in the three-electrode electrochemical test system in a sulfuric acid solution is performed using a PAR4000A electrochemical workstation.

[0060] Furthermore, the reference electrode is further provided with a lead wire 2 connected to the exposed reference electrode body 1 .

[0061] An embodiment of the present invention provides a method for preparing the reference electrode for testing the above-mentioned valve-regulated lead-acid battery, wherein the method comprises: using a silver wire with a diameter of 0.5-2 mm (e.g., 1 mm) as a working electrode, a platinum electrode as an auxiliary electrode, and a saturated calomel electrode as a reference electrode to form a three-electrode electrochemical test system; performing an anodic polarization treatment on the working electrode in the three-electrode electrochemical test system in a sulfuric acid solution, forming a silver sulfate film layer 12 with a length of 100-200 mm (e.g., 125 mm) on the surface of the silver wire, and preparing a reference electrode body 1; wherein the sulfuric acid solution is concentrated sulfuric acid with a mass concentration (based on the total mass of the sulfuric acid solution) of 95%-98% (usually analytical grade sulfuric acid can be selected), and the polarization current density is 5-7 mA / cm 2 , the polarization time is 18-22s; (for example, the sulfuric acid solution is concentrated sulfuric acid with a mass concentration of 95%-98%, and the polarization current density is 6mA / cm 2 , polarization time is 20s); a reference electrode is prepared using the prepared reference electrode body 1.

[0062] Furthermore, the length of the silver wire is 250 mm.

[0063] Furthermore, the silver purity of the silver wire is 99.9 wt % (based on the total mass of the silver wire).

[0064] Furthermore, the step of performing an anodic polarization treatment on the working electrode in the three-electrode electrochemical test system in a sulfuric acid solution is performed using a PAR4000A electrochemical workstation.

[0065] Furthermore, one end of the prepared reference electrode body 1 is connected to the lead wire 2 to prepare a reference electrode for testing a valve-regulated lead-acid battery.

[0066] An embodiment of the present invention provides the use of the reference electrode for testing a valve-regulated lead-acid battery in an electrochemical test of a valve-regulated lead-acid battery electrode.

[0067] Furthermore, the reference electrode for testing the valve-regulated lead-acid battery is inserted into the valve-regulated lead-acid battery so that the exposed reference electrode body 1 of the reference electrode for testing the valve-regulated lead-acid battery contacts the separator for absorbing electrolyte disposed between the positive and negative plates of the valve-regulated lead-acid battery, and then the valve-regulated lead-acid battery electrode electrochemical test is performed using the reference electrode for testing the valve-regulated lead-acid battery as a reference electrode.

[0068] An embodiment of the present invention provides a valve-regulated lead-acid battery having a reference electrode disposed therein, wherein the reference electrode disposed therein adopts the reference electrode for testing the valve-regulated lead-acid battery described above;

[0069] The exposed reference electrode body 1 of the reference electrode for testing the valve-regulated lead-acid battery is in contact with a separator disposed between the positive and negative plates and absorbing electrolyte.

[0070] Experimental Example 1

[0071] This experimental example provides reference electrode A, reference electrode B, reference electrode C, and performance testing of reference electrode A, reference electrode B, reference electrode C.

[0072] The reference electrode A was prepared in the following manner:

[0073] A 99.9% high-purity silver rod is used to prepare a high-purity silver wire with a length of 250 mm and a diameter of 1 mm; a certain amount of sulfuric acid solution is poured into an electrolytic cell for a three-electrode system, and a saturated calomel electrode and a platinum electrode are inserted into the sulfuric acid solution and fixed, and the processed high-purity silver wire is inserted into the sulfuric acid solution and fixed; a three-electrode electrochemical test system is formed with the high-purity silver wire as the working electrode, the platinum electrode as the auxiliary electrode, and the saturated calomel electrode as the reference electrode; a PAR4000A electrochemical workstation is used to perform anodization polarization treatment on the working electrode in the three-electrode electrochemical test system in a sulfuric acid solution, and a silver sulfate film layer with a length of 125 mm is formed on the surface of the high-purity silver wire to prepare a reference electrode body A; wherein the mass concentration of the sulfuric acid solution is 95%, and the polarization current density is 4 mA / cm 2 , the polarization time is 20s; the end of the prepared reference electrode body A away from the silver sulfate film layer is connected to the lead to obtain the reference electrode A.

[0074] The preparation method of reference electrode B is similar to that of reference electrode A, except that the polarization current density is 6 mA / cm 2 .

[0075] The preparation method of reference electrode C is similar to that of reference electrode A, except that the polarization current density is 8 mA / cm 2 .

[0076] The microscopic morphology of the silver sulfate film layer of reference electrode A, reference electrode B, and reference electrode C was tested. The microscopic morphology of the silver sulfate film layer of reference electrode A, reference electrode B, and reference electrode C is as follows: Figure 2A-2C Comparing the microscopic morphology of the silver sulfate film of reference electrode A, reference electrode B, and reference electrode C, it can be seen that under the same polarization time, the polarization current density is 4mA / cm 2 When the silver sulfate film layer is incomplete, the uniformity and density are poor; the polarization current density is 8mA / cm 2 When the silver sulfate film is uneven and pits appear, this should be caused by excessive oxidation due to excessive polarization current density; the polarization current density is 6mA / cm 2 When the silver sulfate film is intact, dense and uniform, the reference electrode can have long-term stable performance in the valve-regulated lead-acid battery and will not corrode too quickly.

[0077] The electrode potential test was performed on reference electrode A, reference electrode B, and reference electrode C. The specific steps include: using the prepared reference electrode A, reference electrode B, and reference electrode C as indicator electrodes, mercury / mercurous sulfate as reference electrode, and performing electrode potential test on the prepared reference electrode A, reference electrode B, and reference electrode C in 5% sulfuric acid solution for 17 consecutive hours. The test results are as follows: Figure 3 As shown. Comparing the electrode potential test results of reference electrode A, reference electrode B, and reference electrode C, it can be seen that the polarization current density is 4mA / cm 2 The electrode potential of the reference electrode A prepared under the above conditions fluctuates greatly, ranging from -157.77 mV to -159.69 mV. Meanwhile, the electrode potential is greater than -159.69 mV, and is the most positive among the reference electrodes A, B, and C. The polarization current density is 6 mA / cm 2 The electrode potential wave of the reference electrode B prepared under the conditions is between -162.35mV and -162.73mV, and the polarization current density is 8mA / cm 2 The electrode potential wave of the reference electrode C prepared under the above conditions is between -161.58 mV and -162.19 mV, the electrode potential fluctuation range is less than 0.6 mV, and the electrode potential is relatively stable.

[0078] Combining the microscopic morphology of the silver sulfate film layer of reference electrode A, reference electrode B, and reference electrode C and the electrode potential test results, it can be seen that the polarization current density is 6mA / cm 2 The reference electrode B prepared under the above conditions has the most complete and dense silver sulfate film layer, the smallest electrode potential fluctuation, and the most negative potential.

[0079] Experimental Example 2

[0080] This experimental example provides reference electrode D, reference electrode E, reference electrode F, and performance testing of reference electrode D, reference electrode E, and reference electrode F.

[0081] The reference electrode D was prepared in the following manner:

[0082] A 99.9% high-purity silver rod is used to prepare a high-purity silver wire with a length of 250 mm and a diameter of 1 mm; a certain amount of sulfuric acid solution is poured into an electrolytic cell for a three-electrode system, and a saturated calomel electrode and a platinum electrode are inserted into the sulfuric acid solution and fixed, and the processed high-purity silver wire is inserted into the sulfuric acid solution and fixed; a three-electrode electrochemical test system is formed with the high-purity silver wire as the working electrode, the platinum electrode as the auxiliary electrode, and the saturated calomel electrode as the reference electrode; a PAR4000A electrochemical workstation is used to perform anodization polarization treatment on the working electrode in the three-electrode electrochemical test system in a sulfuric acid solution, and a silver sulfate film layer with a length of 125 mm is formed on the surface of the high-purity silver wire to prepare a reference electrode body D; wherein the mass concentration of the sulfuric acid solution is 95%, and the polarization current density is 6 mA / cm 2 , the polarization time is 10s; the end of the prepared reference electrode body D away from the silver sulfate film layer is connected to the lead to obtain the reference electrode D.

[0083] The preparation method of reference electrode E is similar to that of reference electrode D, the only difference being that the polarization time is 20 s.

[0084] The preparation method of reference electrode F is similar to that of reference electrode D, except that the polarization time is 30 s.

[0085] The microscopic morphology of the silver sulfate film layer of reference electrode D, reference electrode E, and reference electrode F was tested. The microscopic morphology of the silver sulfate film layer of reference electrode D, reference electrode E, and reference electrode F is as follows: Figure 4A-4CAs shown. By comparing the microscopic morphology of the silver sulfate film layer of reference electrode D, reference electrode E, and reference electrode F, it can be seen that: under the condition of the same current density, when the polarization time is 10s, the polarization time is short, the silver sulfate film layer has just begun to form, and the integrity, uniformity, and density are poor; when the polarization time is 30s, the polarization time is too long, resulting in excessive oxidation, and oxidation pits appear in the silver sulfate film layer; when the polarization time is 20s, the silver sulfate film layer has good integrity, density, and uniformity. Only when the silver sulfate film layer is complete, dense, and uniform, can the reference electrode have long-term stable performance in the valve-regulated lead-acid battery and will not corrode too quickly.

[0086] The electrode potential test of reference electrode D, reference electrode E, and reference electrode F is performed. The specific steps include: using the prepared reference electrode D, reference electrode E, and reference electrode F as indicator electrodes, mercury / mercurous sulfate as reference electrode, and performing electrode potential test on the prepared reference electrode D, reference electrode E, and reference electrode F in 5% sulfuric acid solution for 10 consecutive hours. The test results are as follows: Figure 5 As shown. By comparing the electrode potential test results of reference electrode D, reference electrode E, and reference electrode F, it can be seen that the electrode potential of reference electrode D prepared under the condition of polarization time of 10s has a large fluctuation, and the potential is the most positive among reference electrode D, reference electrode E, and reference electrode F; the electrode potential fluctuation range of reference electrode E and reference electrode F prepared under the conditions of polarization time of 20s and 30s is small (<0.8mV), and the electrode potential is relatively stable.

[0087] Combining the microscopic morphology of the silver sulfate film layer of reference electrode D, reference electrode E, and reference electrode F and the electrode potential test results, it can be seen that the reference electrode E prepared when the polarization time is 20s has the most complete and dense silver sulfate film layer, with small electrode potential fluctuation and negative potential.

[0088] Experimental Example 3

[0089] This experimental example provides reference electrode G-1, reference electrode G-2, reference electrode G-3, reference electrode G-4, reference electrode G-5, reference electrode G-6 and performance testing of each reference electrode.

[0090] The reference electrode G-1 was prepared by the following method:

[0091] A 99.9% high-purity silver rod is used to prepare a high-purity silver wire with a length of 250 mm and a diameter of 1 mm; a certain amount of sulfuric acid solution is poured into an electrolytic cell for a three-electrode system, and a saturated calomel electrode and a platinum electrode are inserted into the sulfuric acid solution and fixed, and the processed high-purity silver wire is inserted into the sulfuric acid solution and fixed; a three-electrode electrochemical test system is formed with the high-purity silver wire as the working electrode, the platinum electrode as the auxiliary electrode, and the saturated calomel electrode as the reference electrode; a PAR4000A electrochemical workstation is used to perform anodization polarization treatment on the working electrode in the three-electrode electrochemical test system in a sulfuric acid solution, and a silver sulfate film layer with a length of 125 mm is formed on the surface of the high-purity silver wire to prepare a reference electrode body D; wherein the mass concentration of the sulfuric acid solution is 95%, and the polarization current density is 6 mA / cm 2 , the polarization time is 20s; the end of the prepared reference electrode body D away from the silver sulfate film layer is connected to the lead to obtain the reference electrode G-1.

[0092] The preparation method of reference electrode G-1 was repeated to prepare reference electrode G-2, reference electrode G-3, reference electrode G-4, reference electrode G-5, and reference electrode G-6.

[0093] Reference electrode G-1, reference electrode G-2, reference electrode G-3, reference electrode G-4, reference electrode G-5, reference electrode G-6 Figure 8 shown.

[0094] The electrode potential test was performed on reference electrode G-1, reference electrode G-2, reference electrode G-3, reference electrode G-4, reference electrode G-5, and reference electrode G-6. The specific steps include: using the prepared reference electrode G-1, reference electrode G-2, reference electrode G-3, reference electrode G-4, reference electrode G-5, and reference electrode G-6 as working electrodes, mercury / mercurous sulfate as reference electrode, and 5% sulfuric acid solution as electrolyte, and using PAR4000A electrochemical workstation to perform stability tests on reference electrode G-1, reference electrode G-2, reference electrode G-3, reference electrode G-4, reference electrode G-5, and reference electrode G-6, respectively, and the test was continued for 40 hours at a test temperature of 22°C. The test results are as follows Figure 6 shown.

[0095] Depend on Figure 6 It can be seen that the electrode potential of reference electrode G-1 and reference electrode G-2 was initially located near -84.3mV, which was due to the incomplete activation of the reference electrode. As the test progressed, the electrode potential gradually decreased, and after 8 hours, it decreased to -165mV, and finally stabilized at around -166.2mV. The electrode potential of reference electrode G-3, reference electrode G-4, reference electrode G-5, and reference electrode G-6 was relatively stable, and the electrode potential fluctuation during the test process did not exceed 2mV.

[0096] From the electrode potential test results of reference electrode G-1, reference electrode G-2, reference electrode G-3, reference electrode G-4, reference electrode G-5, and reference electrode G-6, it can be seen that the electrode potentials of the reference electrodes are within 1 mV after 40 hours of testing, the electrode potential of a single reference electrode is stable, and the differences of the 6 electrodes in the same batch are also small. The test results show that the preparation method of the silver / silver sulfate reference electrode provided by the present invention meets the electrode stability requirements of the reference electrode.

[0097] Experimental Example 4

[0098] This experimental example provides a reference electrode K and a performance test of the reference electrode K.

[0099] The reference electrode K was prepared by the following method:

[0100] A 99.9% high-purity silver rod is used to prepare a high-purity silver wire with a length of 250 mm and a diameter of 1 mm; a certain amount of sulfuric acid solution is poured into an electrolytic cell for a three-electrode system, and a saturated calomel electrode and a platinum electrode are inserted into the sulfuric acid solution and fixed, and the processed high-purity silver wire is inserted into the sulfuric acid solution and fixed; a three-electrode electrochemical test system is formed with the high-purity silver wire as the working electrode, the platinum electrode as the auxiliary electrode, and the saturated calomel electrode as the reference electrode; a PAR4000A electrochemical workstation is used to perform anodization polarization treatment on the working electrode in the three-electrode electrochemical test system in a sulfuric acid solution, and a silver sulfate film layer with a length of 125 mm is formed on the surface of the high-purity silver wire to prepare a reference electrode body D; wherein the mass concentration of the sulfuric acid solution is 95%, and the polarization current density is 6 mA / cm 2 , the polarization time is 20s; the end of the prepared reference electrode body D away from the silver sulfate film layer is connected to the lead to obtain a reference electrode K.

[0101] The reference electrode K was used to perform an electrochemical test on a valve-regulated lead-acid battery electrode. The specific steps include: placing the reference electrode body of the reference electrode K into the valve-regulated lead-acid battery, and contacting the silver sulfate film layer with the separator of the valve-regulated lead-acid battery that absorbs electrolyte between the positive and negative plates. The reference electrode K was used as the reference electrode, and the positive pole of the valve-regulated lead-acid battery was used as the working electrode. The electrode potential of the positive pole of the valve-regulated lead-acid battery was tested for 17 hours using a PAR4000A electrochemical workstation. The test results are as follows: Figure 7 shown.

[0102] The test results show that the electrode potential of the reference electrode K slowly rises from the initial 1.143V after being placed in the valve-regulated lead-acid battery. After 17 hours of testing, the electrode potential stabilizes at around 1.154V, and the electrode potential fluctuates by no more than 0.4mV within 1 hour, indicating that the electrode potential is quite stable. It can be seen that the electrode potential of the reference electrode of the present invention is stable in sulfuric acid solution and industrial valve-regulated lead-acid batteries, and is suitable for use as a reference electrode for electrochemical performance testing of lead-acid batteries.

[0103] Experimental Example 5

[0104] This experimental example provides reference electrode L-1, reference electrode L-2, reference electrode L-3 and valve-regulated lead-acid battery M-1 with reference electrode inside, valve-regulated lead-acid battery M-2 with reference electrode inside, and valve-regulated lead-acid battery M-3 with reference electrode inside.

[0105] The reference electrode L-1 was prepared by the following method:

[0106] A 99.9% high-purity silver rod is used to prepare a high-purity silver wire with a length of 250 mm and a diameter of 1 mm; a certain amount of sulfuric acid solution is poured into an electrolytic cell for a three-electrode system, and a saturated calomel electrode and a platinum electrode are inserted into the sulfuric acid solution and fixed, and the processed high-purity silver wire is inserted into the sulfuric acid solution and fixed; a three-electrode electrochemical test system is formed with the high-purity silver wire as the working electrode, the platinum electrode as the auxiliary electrode, and the saturated calomel electrode as the reference electrode; a PAR4000A electrochemical workstation is used to perform anodization polarization treatment on the working electrode in the three-electrode electrochemical test system in a sulfuric acid solution, and a silver sulfate film layer with a length of 125 mm is formed on the surface of the high-purity silver wire to prepare a reference electrode body L-1; wherein the mass concentration of the sulfuric acid solution is 95%, and the polarization current density is 6 mA / cm 2 , the polarization time is 20s; the end of the prepared reference electrode body L-1 away from the silver sulfate film layer is connected to the lead to obtain the reference electrode L-1.

[0107] The preparation method of reference electrode L-2 is similar to that of reference electrode L-1, the only difference is that the diameter of the silver wire is 2 mm.

[0108] The preparation method of reference electrode L-3 is similar to that of reference electrode L-1, the only difference is that the diameter of the silver wire is 0.4 mm.

[0109] The valve-regulated lead-acid battery M-1 with a reference electrode disposed therein is prepared by the following method:

[0110] The reference electrode body of the reference electrode L-1 is placed inside a purchased valve-regulated lead-acid battery, and the silver sulfate film layer is brought into contact with the separator that absorbs electrolyte and is arranged between the positive and negative plates of the purchased valve-regulated lead-acid battery, thereby obtaining a valve-regulated lead-acid battery M-1 with a reference electrode arranged inside.

[0111] The preparation method of the valve-regulated lead-acid battery M-2 with a reference electrode disposed therein is similar to that of the valve-regulated lead-acid battery M-1 with a reference electrode disposed therein, the only difference being that the reference electrode L-2 is selected.

[0112] The preparation method of the valve-regulated lead-acid battery M-3 with a reference electrode disposed therein is similar to that of the valve-regulated lead-acid battery M-1 with a reference electrode disposed therein, the only difference being that the reference electrode L-3 is selected.

[0113] A valve-regulated lead-acid battery M-1 with a reference electrode inside, a valve-regulated lead-acid battery M-2 with a reference electrode inside, and a valve-regulated lead-acid battery M-3 with a reference electrode inside are used for power supply, and the performance of the valve-regulated lead-acid batteries and the reference electrode is monitored.

[0114] It was finally discovered that: after the reference electrode L-2 was inserted, gaps would appear between the diaphragms, affecting the tightness between the plates and destroying the performance of the valve-regulated lead-acid battery itself; the reference electrode L-3 itself was not strong enough, and after a period of time in the sulfuric acid system inside the valve-regulated lead-acid battery, obvious chemical corrosion would occur, causing a sharp drop in the performance of the reference electrode; after the reference electrode L-1 was inserted, the performance of the valve-regulated lead-acid battery itself was not affected, and the electrode potential of the reference electrode itself was stable.

[0115] Experimental Example 6

[0116] This experimental example provides a reference electrode N and a valve-regulated lead-acid battery O having the reference electrode disposed therein.

[0117] The reference electrode N is prepared by the following method:

[0118] A 99.9% high-purity silver rod is used to prepare a high-purity silver wire with a length of 250 mm and a diameter of 1 mm; a certain amount of sulfuric acid solution is poured into an electrolytic cell for a three-electrode system, and a saturated calomel electrode and a platinum electrode are inserted into the sulfuric acid solution and fixed, and the processed high-purity silver wire is inserted into the sulfuric acid solution and fixed; a three-electrode electrochemical test system is formed with the high-purity silver wire as a working electrode, the platinum electrode as an auxiliary electrode, and the saturated calomel electrode as a reference electrode; a PAR4000A electrochemical workstation is used to perform an anodic polarization treatment on the working electrode in the three-electrode electrochemical test system in a sulfuric acid solution, and a silver sulfate film layer with a length of 125 mm is formed on the surface of the high-purity silver wire to prepare a reference electrode body N; wherein the mass concentration of the sulfuric acid solution is 95%, and the polarization current density is 6 mA / cm 2 , the polarization time is 20s; the end of the prepared reference electrode body N away from the silver sulfate film layer is connected to the lead to obtain the reference electrode N.

[0119] A valve-regulated lead-acid battery O with a reference electrode disposed therein is prepared by the following method:

[0120] The reference electrode body portion of the reference electrode N is placed inside a purchased valve-regulated lead-acid battery, and the silver sulfate film layer portion is brought into contact with a separator that absorbs electrolyte and is disposed between the positive and negative plates of the purchased valve-regulated lead-acid battery, thereby obtaining a valve-regulated lead-acid battery O having a reference electrode disposed therein.

[0121] The purchased valve-regulated lead-acid battery, i.e. the battery before the reference electrode is packaged, is subjected to charge and discharge tests. The valve-regulated lead-acid battery O with a reference electrode inside, i.e. the battery after the reference electrode is packaged, is subjected to charge and discharge tests. The voltage-time curves of the battery charge and discharge process before and after the reference electrode is packaged are shown in FIG. Fig. 9 As shown, the battery capacity-time curve of the battery charge and discharge process before and after the reference electrode packaging is as follows Fig.10 as shown.

[0122] See also Fig. 9 The voltage-time curve of the battery charge and discharge process before the reference electrode is encapsulated is highly consistent with the voltage-time curve of the battery charge and discharge process after the reference electrode is encapsulated. The charge cut-off voltage is around 2.37V and the discharge cut-off voltage is around 1.82. It can be seen that the effect of the reference electrode N encapsulated in the valve-regulated lead-acid battery on the voltage performance of the valve-regulated lead-acid battery is negligible and can be ignored.

[0123] See also Fig.10The capacity-time curve of the battery charge-discharge process before the reference electrode is packaged is highly coincident with the capacity-time curve of the battery charge-discharge process after the reference electrode is packaged. The battery capacity before the reference electrode is packaged is 184.5Ah, and the battery capacity after the reference electrode is packaged is 179.8Ah. Although the reference electrode N is packaged in the valve-regulated lead-acid battery, the battery capacity is slightly attenuated, but the capacity attenuation is only 2.5%, which is within the allowable range. It can be seen that the reference electrode N packaged in the valve-regulated lead-acid battery has little effect on the capacity performance of the battery itself.

[0124] The preferred embodiments of the present invention are described above with reference to the accompanying drawings. Many features and advantages of these embodiments are clear from this detailed description, and therefore the claims are intended to cover all such features and advantages of these embodiments that fall within their true spirit and scope. In addition, since many modifications and changes are easily conceivable to those skilled in the art, it is not intended to limit the embodiments of the present invention to the precise structure and operation illustrated and described, but all suitable modifications and equivalents falling within its scope may be covered.

Claims

1. A reference electrode for testing a valve-regulated lead-acid battery, wherein: The reference electrode is provided with a bare reference electrode body; The exposed reference electrode body is in a filament shape, and is composed of a silver wire and a silver sulfate film layer coated on the surface of the silver wire; The diameter of the silver wire is 0.5-2 mm, and the length of the silver wire coated with the silver sulfate film layer is 100-200 mm; the length of the silver wire is greater than the length of the silver wire coated with the silver sulfate film layer; The silver sulfate film layer is selected from the silver sulfate film layer prepared by the following preparation method: A three-electrode electrochemical test system is formed by using a silver wire as a working electrode, a platinum electrode as an auxiliary electrode, and a saturated calomel electrode as a reference electrode; the working electrode in the three-electrode electrochemical test system is subjected to an anodic polarization treatment in a sulfuric acid solution to form the silver sulfate film layer on the surface of the silver wire; wherein the sulfuric acid solution is concentrated sulfuric acid with a mass concentration of 95%-98%, and a polarization current density of 5-7 mA / cm 2 , polarization time is 18-22s.

2. The reference electrode according to claim 1, wherein The diameter of the silver wire of the reference electrode body is 1 mm; The length of the silver wire coated with the silver sulfate film is 125 mm; The sulfuric acid solution is analytical pure sulfuric acid, and the polarization current density is 6 mA / cm 2 , polarization time is 20s; The length of the exposed reference electrode body is 250 mm.

3. The reference electrode according to claim 1, wherein The silver purity of the silver wire of the reference electrode body is 99.9 wt %.

4. The reference electrode according to claim 1, wherein The reference electrode is further provided with a lead wire connected to the exposed reference electrode body.

5. The reference electrode according to claim 1, wherein The step of performing an anodic polarization treatment on the working electrode in the three-electrode electrochemical test system in a sulfuric acid solution is performed using a PAR4000A electrochemical workstation.

6. The method for preparing a reference electrode for testing a valve-regulated lead-acid battery according to any one of claims 1 to 5, wherein: The method includes: A three-electrode electrochemical test system was constructed with a silver wire as the working electrode, a platinum electrode as the auxiliary electrode, and a saturated calomel electrode as the reference electrode. The working electrode in the three-electrode electrochemical test system is subjected to anodizing treatment in a sulfuric acid solution to form a silver sulfate film on the surface of the silver wire to prepare a reference electrode body; wherein the sulfuric acid solution is concentrated sulfuric acid with a mass concentration of 95%-98%, and the polarization current density is 5-7 mA / cm 2 , polarization time is 18-22s; The reference electrode body prepared as the exposed reference electrode body is used to prepare the reference electrode for testing the valve-regulated lead-acid battery.

7. The preparation method according to claim 6, wherein: The sulfuric acid solution is concentrated sulfuric acid for analysis, and the polarization current density is 6 mA / cm 2 , polarization time is 20s; The length of the silver wire is 250 mm; The silver purity of the silver wire is 99.9wt%; The step of performing an anodic polarization treatment on the working electrode in the three-electrode electrochemical test system in a sulfuric acid solution is performed using a PAR4000A electrochemical workstation.

8. The preparation method according to claim 6, wherein: The reference electrode for testing a valve-regulated lead-acid battery is prepared by using the prepared reference electrode body as the exposed reference electrode body in the following manner: one end of the prepared reference electrode body is connected to a lead wire to prepare a reference electrode for testing a valve-regulated lead-acid battery.

9. Use of the reference electrode for testing valve-regulated lead-acid batteries according to any one of claims 1 to 5 in electrochemical testing of valve-regulated lead-acid battery electrodes.

10. The use according to claim 9, wherein: Insert the reference electrode for testing the valve-regulated lead-acid battery into the valve-regulated lead-acid battery so that the exposed reference electrode body of the reference electrode for testing the valve-regulated lead-acid battery contacts the separator for absorbing electrolyte disposed between the positive and negative plates of the valve-regulated lead-acid battery, and then use the reference electrode for testing the valve-regulated lead-acid battery as a reference electrode to perform an electrochemical test on the valve-regulated lead-acid battery electrode.

11. A valve-regulated lead-acid battery, wherein: The valve-regulated lead-acid battery is provided with a reference electrode inside, and the reference electrode provided inside the valve-regulated lead-acid battery is the reference electrode for testing the valve-regulated lead-acid battery according to any one of claims 1 to 5; In the valve-regulated lead-acid battery, the silver sulfate film layer of the exposed reference electrode body of the reference electrode contacts a separator disposed between the positive and negative plates and absorbing electrolyte.

Citation Information

Patent Citations

  • Solid-state reference electrode and preparation method thereof

    CN105375037A

  • Lead battery comprising an integrated reference electrode

    WO2004019022A1